Interpesonal Meaning In TOEFL Test Direction - Ruminda; Latifah, Khaerunnisa Siti (Jurnal Sastra - Studi Ilmiah Sastra, 2022)
Interpersonal meanings are meanings which express a speaker’s attitudes and judgments which is realized through the system of MOOD. This study investigates the interpersonal meaning in TOEFL test direction. This study utilized descriptive qualitative method. Meanwhile, the data were collected from TOEFL test preparation book by Pyle, M.A. and Page, M.E.M. (1995). CLIFFS’s TOEFL Preparation Guide. This study use Halliday and Matthiessen’s theory about interpersonal meaning. . Based on the results, the researcher can be taken a conclusion that in the direction of TOEFL test there is ten clauses of statement clause and six clauses of command clauses, meanwhile offer and question clauses is not found tn the direction.